Inverse Born series for the radiative transport equation. (September 2015) - Machida, Manabu; Schotland, John C
Abstract We propose a direct reconstruction method for the inverse transport problem that is based on inversion of the Born series. We characterize the approximation error of the method and illustrate its use in numerical simulations.